2010
DOI: 10.1007/s10764-010-9464-9
|View full text |Cite
|
Sign up to set email alerts
|

Mantled Howler (Alouatta palliata) Arboreal Pathway Networks: Relative Impacts of Resource Availability and Forest Structure

Abstract: Numerous studies have concluded that primates move about their environments in a nonrandom manner, frequently traveling between consecutive foraging sites along relatively straight-line paths. However, primates do not always take the most direct path between resources, and a number of species have been observed to travel repeatedly along a network of the same arboreal pathways. In this study, I used spatially explicit techniques to examine quantitatively what mantled howler monkey groups on Barro Colorado Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 78 publications
3
32
0
Order By: Relevance
“…Studies that failed to demonstrate a positive relationship for howlers in general (among other folivorous primates) attributed this result to a weak or absent food competition and/or a reliance on alternative, fallback food items, such as mature leaves (Isbell 1991 ;Janson and Goldsmith 1995 ). A signifi cant relationship was found in four out of seven studies that evaluated this aspect at the species level, particularly in A. palliata (Larose 1996 ;Williams-Guilén 2003 ;Hopkins 2011 ), the howler monkey that forms the largest groups and presents the wider variation in group size (see . The fourth study that found this relationship involved a population of A. pigra at the Community Baboon Sanctuary (Ostro et al 1999a ).…”
Section: Factors Affecting Day Rangementioning
confidence: 99%
See 2 more Smart Citations
“…Studies that failed to demonstrate a positive relationship for howlers in general (among other folivorous primates) attributed this result to a weak or absent food competition and/or a reliance on alternative, fallback food items, such as mature leaves (Isbell 1991 ;Janson and Goldsmith 1995 ). A signifi cant relationship was found in four out of seven studies that evaluated this aspect at the species level, particularly in A. palliata (Larose 1996 ;Williams-Guilén 2003 ;Hopkins 2011 ), the howler monkey that forms the largest groups and presents the wider variation in group size (see . The fourth study that found this relationship involved a population of A. pigra at the Community Baboon Sanctuary (Ostro et al 1999a ).…”
Section: Factors Affecting Day Rangementioning
confidence: 99%
“…These studies tested predictions such as (1) howlers minimize ("optimize") the distance traveled by using straightline movements to the nearest available tree of a few target species; (2) they monitor the availability of large and/or preferred food sources, and exploit the most productive trees available; (3) they repeatedly use travel pathways that include large trees that provide more food and from where they enjoy enhanced visibility of the surroundings, thereby reducing the need for memory load; and (4) they use these tall (high-visibility) trees where different routes intersect as nodes or decision points, an indication of a topological mental representation ( A. caraya : Ventura 2004( A. caraya : Ventura , 2005A. palliata : Garber and Jelinek 2006 ;Hopkins 2008Hopkins , 2011A. g. clamitans : Pereira 2008 ).…”
Section: Spatial Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. caraya has even been reported consuming wild and domestic birds' eggs (Bicca-Marques et al 2009 ). Howler monkeys appear to choose travel pathways with higher resource availability than comparable straightline paths (Hopkins 2011 ), and those living in forest fragments have been known to gather as much as 20 % of their total annual diet from outside their home patch (Asensio et al 2009 ). Therefore, while the only howler monkey species currently recognized as a crop-raider is A. palliata (McKinney 2010 ), the wide distribution and dietary fl exibility of the genus suggests that the prevalence of crop-raiding in this group is likely to be much higher.…”
Section: Crop-raiding By Primatesmentioning
confidence: 99%
“…In particular, vegetation structure (e.g. Dial et al, 2006;Hopkins, 2011;Lambert et al, 2006;Malcolm, 1997;Pardini et al, 2005), as well as the structure of the leaf litter (e.g. Naxara et al, 2009;Sayer et al, 2010;Van Sluys et al, 2007;Vonesh, 2001) and woody debris (e.g.…”
Section: Introductionmentioning
confidence: 99%